MolViewSpec: a Mol* extension for describing and sharing molecular visualizations - Midlik, Adam; Bittrich, Sebastian; Fleming, Jennifer R; Nair, Sreenath; Velankar, Sameer; Burley, Stephen K; Young, Jasmine Y; Vallat, Brinda; Sehnal, David (Nucleic acids research, 2025)
Data visualization is a pivotal component of a structural biologist's arsenal. The Mol* Viewer makes molecular visualizations available to broader audiences via most web browsers. While Mol* provides a wide range of functionality, it has a steep learning curve and is only available via a JavaScript interface. To enhance the accessibility and usability of web-based molecular visualization, we introduce MolViewSpec (molstar.org/mol-view-spec), a standardized approach for defining molecular visualizations that decouples the definition of complex molecular scenes from their rendering. Scene definition can include references to commonly used structural, volumetric, and annotation data formats together with a description of how the data should be visualized and paired with optional annotations specifying colors, labels, measurements, and custom 3D geometries. Developed as an open standard, this solution paves the way for broader interoperability and support across different programming languages and molecular viewers, enabling more streamlined, standardized, and reproducible visual molecular analyses. MolViewSpec is freely available as a Mol* extension and a standalone Python package.
Keywords: Software; software; Computer Graphics; uživatelské rozhraní počítače; User-Computer Interface; internet; počítačová grafika; Internet